TURİZM EĞİTİMİNDE WEB TABANLI ÖĞRETİMİN ÖĞRENCİ BAŞARISINA ETKİSİ (GAZİANTEP ÜNİVERSİTESİ TURİZM VE OTELCİLİK MESLEK YÜKSEKOKULU ÖRNEĞİ) - OLCAY, ATINÇ (Fırat Üniveristesi, 2011)
Araştırma, 2009-2010 akademik yılı güz döneminde Gaziantep il merkezinde bulunan Gaziantep Üniversitesi Turizm ve Otelcilik Meslek Yüksekokulu Turizm ve Seyahat İşletmeciliği Programı ile Turizm ve Otel İşletmeciliği Programında öğrenim gören toplam 50 (25 deney grubu, 25 kontrol grubu) öğrenci üzerinde yapılmıştır. Araştırma öntest-sontest ve deney-kontrol grubu desenine uygun olarak yürütülmüştür. Deney ve kontrol grupları oluşturulurken yansızlık; öğrenci başarısı, internet erişimi, web tabanlı öğrenme yöntemi bilgi düzeyi ile bilgisayar ve internet kullanım bilgi düzeyi ölçütleriyle sağlanmıştır.GTOİ/SEYH 111 İletişim Dersinin; temel kavramlar, sözel iletişim, sözsüz iletişim, yazılı iletişim ile iş yaşamı ve iletişim konuları deney grubuna web tabanlı öğretim yöntemiyle, kontrol grubuna ise geleneksel yöntem ile sekiz hafta süreyle aktarılmıştır. Diğer taraftan nitel yöntem içerisinde görüş belirleme formları yorumlanmıştır.Anahtar Kelimeler: Web Tabanlı Öğretim, Başarı, Turizm Eğitimi.

The purpose of this research is to determine the effects to the success of higher education students who are in the field of tourism education with web-based teaching method in 2009-2010 academic year, fall semester.This research was carried out on 50 (25 students for control group, 25 students for experimental group) students who are training in Tourism and Hotel Hospitality Vocational College and Tourism and Travel Management Program in Gaziantep University. The research was conducted according to pre. Test-post.test and experimental control group model. Creating control and experimental group, neutrality has been provided in the criteria of academic success, internet Access, the method of web based learning and knowledge level of using internet and computer.In communication course; basic concepts, verbal-nonverbal communication, written communication with the communication issues by web-based teaching method. Were transferred to the experimental group for eight weeks conventional method such as plain language, question-answer was transferred to the control group as well. On the other hand, thrıough opinion form had been interpreted by simple content analysis.Key Words: Web-based Teaching, Success, Tourism Education.
In tourism education web- based teaching influence students? success (Gaziantep University Vocational School of Tourism and Hotel Management case)
Keywords: Eğitim ve Öğretim